Numerical Analysis of the Effect of S-Shaped Duct Key Geometry Parameters on the Inlet Distortion of Distributed Ducted Fans - Wei Jia; Guanghui Li; Tao Liu; Qingguo Kong; Shuiting Ding (Aerospace)
Distributed propulsion systems are strategically placed along the aircraft wingspan to ingest the fuselage boundary layer, thereby enhancing propulsion efficiency. However, the aerodynamic effects of S-shaped duct geometry on a distributed propulsion system are not fully understood. The impact of the S-shaped duct inlet aspect ratio and centerline offset on the inlet distortion of ducted fans was numerically investigated using a method based on the circumferential body force model. The results show that the most severe inlet distortion occurs when a large centerline offset is combined with a small aspect ratio. For an S-shaped duct with a substantial centerline offset, increasing the aspect ratio mitigates the distortion level in the edge fans. Specifically, increasing the aspect ratio from 6 to 10 reduces the total pressure and swirl distortion index in the edge fan by up to 80.1% and 84.2%, respectively. In an S-shaped duct with a small aspect ratio, decreasing the centerline offset from 1.75 times to 0.75 times the ducted fan diameter lowers the total pressure and swirl distortion index in the edge fan by up to 75.2% and 87.5%, respectively. These insights provide valuable information for the integrated design and optimization of the S-shaped duct in distributed propulsion systems.